The effect of social norms on bribe offers - Abbink, Klaus (2018)
We report a sequential bribery game to disentangle the effect of descriptive social norms among public officials on bribe offers by firms. Participants who knew that they were interacting with a partner from a group with a majority of corrupt (as opposed to honest) partners offered twice as many bribes. This effect of norms occurred independently of strategic considerations and the possibility of being sanctioned. Indeed, the effect of sanctions was not significant. These findings highlight a causal connection from perceptions of bribery to actual behavior.